Fig. 1 in Two New Species of Free-living Marine Nematodes (Nematoda: Axonolaimidae and Tripyloididae) from the Coast of Antarctica - Shimada, Daisuke; Suzuki, Atsushi C.; Tsujimoto, Megumu; Imura, Satoshi; Kakui, Keiichi (Zenodo, 2021)
Fig. 1. Odontophora odontophoroides sp. nov. A, male body (holotype); B, male anterior region (holotype); C, male head with closed mouth (holotype); D, male posterior region (holotype); E, male genital apparatus (holotype); F, G, spicule and gubernaculum (ICHUM 5486 and 5488, respectively). Abbreviations: a.t., anterior testis; e.g., ejaculatory glands; p.p., precloacal pore; p.s., precloacal supplement; p.t., posterior testis; s.v., seminal vesicle; v.d., vas deferens. Scale bars: A, 500 µm; B, D, 100 µm; C, 20 µm; E–G, 10 µm. : Published as part of Shimada, Daisuke, Suzuki, Atsushi C., Tsujimoto, Megumu, Imura, Satoshi & Kakui, Keiichi, 2021, Two New Species of Free-living Marine Nematodes (Nematoda: Axonolaimidae and Tripyloididae) from the Coast of Antarctica, pp. 49-63 in Species Diversity 26 (1) on page 52, DOI: 10.12782/specdiv.26.49, http://zenodo.org/record/5736867